Involuntary integration in public education, fertility and human capital - Leonid V. Azarnert (Bar-Ilan University, Department of Economics, 2008)
This article analyzes the negative side of involuntary integration in public education - its effect on whites. The model shows that the flight from the integrated multicultural public schools to private education increases private educational expenditures and decreases fertility among more affluent whites whose children flee. In contrast, among less prosperous parents multicultural integration in public education decreases their children's human capital levels. The analysis also demonstrates that among whites the poor, who can not afford to avoid the forcible integration, suffer from a higher negative effect than the rich, who can resort to the White Flight.
Keywords: I2; J1; 330; Education; Integration policy; White Flight; Fertility; Human capital; Soziale Integration; Bildungschancen; Weiße; Fertilität; Humankapital; Israel